Utility Rate Regulation: The Little Locomotive That Couldn’t - Neil N. Bernstein (Washington University Law Quarterly, 1970)
The thesis of this Article is that rate base regulation is a vestigial remnant of nineteenth-century jurisprudential notions that have since been repudiated by the Supreme Court. In addition, this kind of regulation serves no beneficial purpose in today's society and should be discarded in favor of more meaningful rate appraisal standards.
Keywords: Rate regulation; Utilities